Profiling of serum and tissue high abundance acute-phase proteins of patients with epithelial and germ line ovarian carcinoma - Chen, Y.; Lim, B.; Peh, S.; Abdul-Rahman, Puteri Shafinaz; Hashim, Onn Haji (BMC, 2008)
Patients with EOCa and GOCa demonstrated distinctive aberrant expression of serum and tissue high abundance acute-phase proteins compared to negative control women.